Variation of heavy metal accumulation in certain landscaping plants due to traffic density - Turkyilmaz, Aydin; Cetin, Mehmet; Sevik, Hakan; Isinkaralar, Kaan; Saleh, Elnaji A. Ahmaida (Springer Science and Business Media LLC, 2018)
Air pollution is one of the biggest problems of urban environments today. Heavy metals are particularly important in terms of components that pollute the air. This is due to the reason that heavy metals can stay in nature for a long time without being disintegrated, and their concentration in the environment is constantly increasing. They also tend to bioaccumulate. Therefore, determination of the heavy metal concentration is crucial for identifying high-risk areas and the level of risk. Plants are generally used as biomonitors for determining heavy metal concentration in the air. Determination of heavy metal concentrations in plants is crucial in determining the ability of plants to remove heavy metals from the air, and thus being used as a means of increasing air quality, as well as monitoring air quality. The aim of this study was to determine the variation of different heavy metal concentrations depending on traffic density in certain landscape plants collected from areas where traffic density is at different levels. For this purpose, leaf samples of Salix babylonica, Robinia pseudoacacia, Sophora japonica, and Aesculus hippocastanum, which are frequently used in landscaping studies, were collected from individuals where there was dense traffic, less dense traffic, and almost no traffic, and the quantities of Pb, Cu, Ca, Mg, Cd, Cr, Ni, Fe, Mn, and Zn were determined by heavy metal analysis. Based on the results, the highest mean values of Cd, Ni, and Zn were found in S. babylonica, highest mean values of Pb and Mn were found in A. hippocastanum, and those of other elements were found in S. japonica. In areas with a high traffic density; the highest values of Cd, Ni and Zn were found in S. babylonica and the highest values of Cu, Mg, Cr, Fe and Mn were found in S. japonica. In areas with high traffic density, only the highest value of Pb was found in A. hippocastanum and the highest value of Ca was found in R. pseudoacacia. Based on these results, it can be concluded that S. babylonica and S. japonica are good bioindicators.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water